Interface Phenomena. Issue 24 (8th November 2021) - Engstfeld, Albert K.; Hoster, Harry; Magnussen, Olaf M.
Abstract : This special collection on Interface Phenomena is dedicated to R. Jürgen Behm on the occasion of his retirement and 70th birthday. Jürgen Behm's research over the past 40 years has addressed a wide variety of interface processes in the fields of growth, corrosion, heterogeneous catalysis, electrocatalysis, and batteries.